Understanding Tuberculosis Transmission in the United Kingdom: Findings From 6 Years of Mycobacterial Interspersed Repetitive Unit–Variable Number Tandem Repeats Strain Typing, 2010–2015. Issue 10 (7th June 2018) - Davidson, Jennifer A; Thomas, H Lucy; Maguire, Helen; Brown, Timothy; Burkitt, Andy; Macdonald, Neil; Campbell, Colin N J; Lalor, Maeve K
Abstract: Genotyping provides the opportunity to better understand tuberculosis (TB) transmission. We utilized strain typing data to assess trends in the proportion of clustering and identify the characteristics of individuals and clusters associated with recent United Kingdom (UK) transmission. In this retrospective cohort analysis, we included all culture-confirmed strain-typed TB notifications from the UK between 2010 and 2015 to estimate the proportion of patients that clustered over time. We explored the characteristics of patients in a cluster using multivariable logistic regression. Overall, 58.5% of TB patients were concentrated in 2, 701 clusters. The proportion of patients in a cluster decreased between 2010 (58.7%) and 2015 (55.3%) ( P = 0.001). Being a clustered patient was associated with being male and UK-born, having pulmonary disease, having a previous TB diagnosis, and having a history of drug misuse or imprisonment. Our results suggest that TB transmission in the UK decreased between 2010 and 2015, during which time TB incidence also decreased. Targeted cluster investigation and extended contact tracing should be aimed at persons at risk of being in a transmission chain, including UK-born individuals with social risk factors in clusters with a high proportion of patients having pulmonary disease.